De silêncios e resistências: sonâmbulas, magnetizadoras e outras esquecidas do espiritismo brasileiro - Veronese, Michelle Marinho (2017)
This research stems from the following questions: Why do women appear so little in the historical narratives of Brazilian Spiritism? Were they, in fact, secondary figures, almost absent in the early years of this religion, or was their presence silenced, hidden behind a history written by men? To answer these questions, I searched for the 19th century women that became involved with magnetism and somnambulism, fringe practices bordering science and religion which influenced Spiritism. I also brought to light profiles of women who were involved with the first Brazilian Spiritist groups and experiments, such as the writing and medical mediums. The methodology includes a qualitative research with analysis of newspapers, chronicles and travelers' reports published in the nineteenth century to build the socio-historical context and the classification presented. Among the authors who illuminate this work, are Bourdieu and his concepts of habitus and religious field; Michelle Perrot, who analyzed silenced women in history, and Joan Scott, with her proposal for the use of the gender category. Authors who discussed secularization, Brazilian religious field and relations between gender and religions also serve as a theoretical reference. My thesis is that Brazilian Spiritism, in the writing of its history referring to the nineteenth century, relegated women to a secondary role as mere assistants, silencing their voices and experiences